Service Delivery in the Healthcare and Educational Systems for Children Following Traumatic Brain Injury: Gaps in Care. Issue 6 (November 2017) - Haarbauer-Krupa, Juliet; Ciccia, Angela; Dodd, Jonathan; Ettel, Deborah; Kurowski, Brad; Lumba-Brown, Angela; Suskauer, Stacy
Abstract : Objective: To provide a review of evidence and consensus-based description of healthcare and educational service delivery and related recommendations for children with traumatic brain injury. Methods: Literature review and group discussion of best practices in management of children with traumatic brain injury (TBI) was performed to facilitate consensus-based recommendations from the American Congress on Rehabilitation Medicine's Pediatric and Adolescent Task Force on Brain Injury. This group represented pediatric researchers in public health, medicine, psychology, rehabilitation, and education. Results: Care for children with TBI in healthcare and educational systems is not well coordinated or integrated, resulting in increased risk for poor outcomes. Potential solutions include identifying at-risk children following TBI, evaluating their need for rehabilitation and transitional services, and improving utilization of educational services that support children across the lifespan. Conclusion: Children with TBI are at risk for long-term consequences requiring management as well as monitoring following the injury. Current systems of care have challenges and inconsistencies leading to gaps in service delivery. Further efforts to improve knowledge of the long-term TBI effects in children, child and family needs, and identify best practices in pathways of care are essential for optimal care of children following TBI.